The impact of urbanization and wealth on house dust mite sensitization in children from north-central Nigeria - Chiara Zuiani; Michele Arigliani; Ramatu Zubair; Livingstone Gayus Dogara; Luigi Castriotta; Ashel Dache Sunday; Reward Christopher Audu; Habibah Dadan-Garba; Zakary Sani; Baba Inusa; Paola Cogo (BMC, 2022)
Abstract The impact of socio-economic status on the risk of allergy in African children is not clear. This was a cross sectional study including children aged 6-14 years from urban and rural settings in north-central Nigeria. Participants underwent skin prick tests to house dust mite (HDM) and an interview investigating socio-economic status through the Family Affluence Scale (FAS) based on a score of 0-6. A total of 346 children were enrolled (52.8% boys; mean age ± SD 9.6 ± 2.0 years), including 142 (41% of total) rural and 204 (59% of total) urban pupils. Prevalence of HDM sensitivity was 2.8% (4/142) in the rural setting and 15.6% (32/204) in the urban setting (P < 0.001). Among urban children, frequency of HDM sensitization was 8.6% (7/81) in the lowest socio-economic group (FAS 0-1), 13.1% (8/61) in the intermediate one (FAS 2-3) and 27.4% (17/62) in the highest one (FAS ≥ 4). Urbanization and increasing wealth are associated with a higher frequency of sensitization to HDM in Nigerian children.